MPC-based approach to active steering for autonomous vehicle systems. (28th November 2005) - Borrelli, F.; Falcone, P.; Keviczky, T.; Asgari, J.; , D. Hrovat
In this paper, a novel approach to autonomous steering systems is presented. A model predictive control (MPC) scheme is designed in order to stabilise a vehicle along a desired path while fulfilling its physical constraints. Simulation results show the benefits of the systematic control methodology used. In particular we show how very effective steering manoeuvres are obtained as a result of the MPC feedback policy. Moreover, we highlight the trade off between the vehicle speed and the required preview on the desired path in order to stabilise the vehicle. The paper concludes with highlights on future research and on the necessary steps for experimental validation of the approach.